EFEKTIVITAS PEMBELAJARAN AKTIF MELALUI PENERAPAN MODEL PEMBELAJARAN KOLABORATIF (COLLABORATIVE LEARNING) UNTUK MENINGKATKAN PRESTASI BELAJAR AKUNTANSI SEKTOR PUBLIK POKOK BAHASAN AKUNTANSI SATUAN KERJA PENGELOLA KEUANGAN DAERAH (SKPKD) - Handayani, Bestari Dwi (Dinamika Pendidikan, 2011)
The study was based on the real lecture of public sector accounting especially accounting for SKPKD process. During the lecture, most of the students did not participate actively. They did not show their self awareness in learning. Based on reality above, it is needed to know whether the collaborative learning model can improve studentsâ self awareness in learning or not. Thus, the objective of this study is to get the description of the teaching experience by applying the collaborative laerning model to improve studentsâ capability. This study is a pre-experiment study. The subjects of this study are four classes: two classes are the experimental groups with collaborative learning model as the treatment ant the rest two classes as the control group with conventional model learning. The participants are the sixth semester students of Accounting Department, Economics Faculty, Semarang State University. The sample t-test were used to analyze the data. The result of this study showed that the use of collaborative learning model can improve the studentsâ self awareness in learning because they were free to decide their own learning objectives and sources. All students in experimental groups were active in decision making.